Om videnskabelighed og tradition i læsningen af Det Nye Testamente - Engberg-Pedersen, Troels (Dansk Teologisk Tidsskrift, 2017)
This article responds to an extensive review article by Jesper Tang Nielsen (Dansk Teologisk Tidsskrift 80, 2017, 51-69) of the present author’s book, John and Philosophy. A New Reading of the Fourth Gospel, by addressing the relationship between scientific scholarship and tradition in the interpretation of The New Testament. While postmodernists of various sorts may wish to deduce from the principle (as quoted by Tang Nielsen from Gitte Buch-Hansen) that ‘truth (without inverted commas) is now perceived as conditional on the method/perspective applied’ (a principle which taken by itself is almost a truism) that there is no longer any need to discuss the method or perspective to be applied, the article argues that there is precisely a need to discuss methods and perspectives and that the history – in the sense of the development – of scholarship plays a crucial role in this discussion. John and Philosophy extensively engages in just that discussion, and for that reason Tang Nielsen’s description of the book’s ‘stoicizing’ and ‘(narrative-)philosophical’ method or perspective as being ultimately based on its author’s choice does not do justice to the book’s aim. In showing this, the article seeks to advance the cause of scientific scholarship as against all other, more directly ‘interested’ readings of The New Testament, including more traditional ones.